Automatic FE modeler using stiffener-based mesh generation algorithm for ship structural analysis - Jang, Beom-Seon; Suh, Yong-Suk; Kim, Eun-Ki; Lee, Tae-Hee (Marine structures, 2008)
Shipbuilding industries have started to employ 3D CAD systems to integrate all design and production processes by achieving seamless data transfer and data sharing. The emerging 3D CAD system brings a considerable change in FE analysis field. The availability of 3D geometry increased the recognition of the need for developing automatic FE modeling system consequently. However, general automatic mesh algorithms developed by academic research field have a limitation. The difficulty in satisfying lots of line constraints and the absence of proper idealization of 3D geometry entities defined in CAD system hinders directly employing the general mesh algorithms. In this research, an automatic FE modeling system has been developed for cargo hold FE modeling and whole ship FE modeling. The basic concept of the algorithm is to decompose surfaces using stiffener lines into subregions and generate mesh using a rule established based on FE modeling practice of ship structure. Since the decomposed subregions take simple polygon, they can be easily transformed into elements by decomposing the polygon according to the rule defined considering the shape of the polygon and mesh seed on its perimeter. The algorithm is also designed to treat appropriate geometry idealizations for bracket-type surface and stiffener connections. The idealization process is also completely customized based on FE modeling practice. The validity of the developed system is verified through illustrative examples.